Evaluation of the antifactor XA chromogenic assay for measuring rivaroxaban plasma concentrations using calibrators and controls. Issue 2 (12th March 2012) - Samama, M.; Contant, G.; Spiro, T.E.; Perzborn, E.; Guinet, C.; Gourmelin, Y.; Le Flem, L.; Rohde, G.; Martinoli, J.L.
Abstract : Background: Rivaroxaban is an oral, direct Factor Xa inhibitor approved for clinical use for the prevention and treatment of thromboembolic disorders across several indications. Routine coagulation monitoring is not required, but a quantitative determination of rivaroxaban concentrations might be useful in some clinical circumstances. Purpose: This multicentre study evaluated the suitability of a modified antifactor Xa chromogenic assay for the measurement of plasma rivaroxaban concentrations (ng/ml) using rivaroxaban calibrators and controls, and to assess the inter-laboratory precision of the measurement. Materials and methods: Twenty-four centres in Europe and North America were provided with sets of rivaroxaban calibrators (0, 41, 209 and 422 ng/ml) and rivaroxaban pooled human plasma controls (20, 199 and 662 ng/ml; the concentrations were unknown to the participating laboratories). The evaluation was carried out over 10 days by each laboratory using local antifactor Xa reagents as well as a centrally provided, modified STA Rotachrom assay (Diagnostica Stago, Asnières-sur-Seine, France). A calibration curve was produced each day, and day-to-day precision was evaluated by testing three human plasma controls. Results: When using the local antifactor Xa reagents, the measured rivaroxaban concentrations (mean±SD/actual value) were 17±6.4/20, 205±28.2/199 and 668±94.4 (in diluted samples)/662 ng/ml, and the coefficients of variance (CV) were 37.0%, 13.7% and 14.1%, respectively. When the modified STA Rotachrom method was used, the measured±SD/actual values were 18±3.4/20, 199±21.7/199 and 656±65.8 (in diluted samples)/662 ng/ml and the CV were 19.1%, 10.9% and 10.0%, respectively. Satisfactory inter-laboratory precision was achieved using rivaroxaban calibrators regardless of the type of antifactor Xa reagent and instrument used, except for the lowest concentration tested (20 ng/ml) when using the different local reagent/instrument combinations. Conclusions: The results indicate that the antifactor Xa chromogenic method is suitable for measuring a wide range of plasma rivaroxaban concentrations (20–660 ng/ml), covering the expected concentrations after therapeutic doses, by using rivaroxaban calibrators and controls.